Automated Powder Filler Machine - Zahmani, Qamar Fairuz; Abdul Latif, Mohd Faruq; Nordin, Abdul Khahar; Katijan, Adnan; Aziz, Azwan; Parnon, Mohamad Afiq Amiruddin; Mokhtar, Siti Nor’ain (UTeM, 2019)
An automotive powder filling machine is a device specially designed to help facilitate the process of weighing, mixing, and packing in one machine. The work of providing flour products undertaken manually where the manufacturing process became inconsistent, time-consuming and required a large number of workers overall. The problem faced by the company Noni Aneka Talam is that the process involves weighing the main ingredients, mixing and packing manually. Also, the company has issues in inconsistent quality control due to manual processes such as measurement error.Companies need technology capable of incorporating different types of flour, sugar and salt accordingly, wrapped continuously in plastic, sealed, fast-labelled, easy to manage and use minimal energy.